Assessment of Tobacco Fields for the Prevalence of Verticillium dahliae in District Swabi, Pakistan - Tasiq Ahmad; Said Akram; Shah Fahad; Muhammad Ilyas; Mukhtar Alam; Hazrat Hussain; Latifur Rehman (AGRIVITA, Journal of Agricultural Science, 2023)
Field and laboratory investigations of tobacco plants were carried out to analyze the distribution of Verticillium wilt caused by V. dahliae. V. dahliae is isolated from field Z (Tarkhai, Yarhussain region of Swabi). Species of Fusarium and Actinomycetes were detected in field B (Shaheedan, Yarhussain region of Swabi), while no V. dahliae was isolated from these fields. V. dahliae was identified based on its colony and conidia morphology. The colony was white, having oval spores and septate mycelium with phialides. The isolate also produced irregularly elongated dark brown to black color microsclerotia of various sizes. The spores count for V. dahliae isolate was 3.61 Ã— 108 conidia/ml. The average colony diameter of V. dahliae after 9 days of incubation on PDA and CM media was 6.55 cm and 5.5 cm, respectively. The biology of Verticillium spp. in tobacco plants and soil in Swabi has not been studied. For the first time, this study reported the presence of V. dahliae in the tobacco fields of Swabi, KPK Pakistan. Detection and isolation of V. dahliae from field soil are necessary for studying the ecology and virulence and creating deterrent control strategies for Verticillium wilt diseases.